Interperasi Kata Qātilū dalam Q.S. Al-Taubah (9): 29 Studi Analisis Kajian Ma‘nā cum Maghzā Sahiron Syamsuddin - Fabrori, Fahri Muhaimin (IAIN Madura, 2023)
The verses of the Al-Quran have meanings and purposes related to the history behind the revelation of the verses. The meaning of verses can be explored by various approaches and methods of interpretation. This article examines the word qātilū in Q.S. At-Taubaḥ [9]: 29. The word often has a double meaning so it is understood incorrectly and only the external aspects are discussed. Basically the word qātilū in the Koran means